2023
DOI: 10.3389/fnmol.2023.1274822
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of mechanotransduction complex genes in auditory/vestibular hair cells in zebrafish

Eliot T. Smith,
Peng Sun,
Shengyang Kevin Yu
et al.

Abstract: Ciliated sensory cells such as photo- and olfactory receptors employ multiple types of opsins or hundreds of unique olfactory G-protein coupled receptors to respond to various wavelengths of light or odorants. With respect to hearing and balance, the mechanotransduction machinery involves fewer variants; however, emerging evidence suggests that specialization occurs at the molecular level. To address how the mechanotransduction complex varies in the inner ear, we characterized the expression of paralogous gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…For example, the high-confidence orthologs clic5a (Clic5), encodes an intracellular chloride channel protein that localizes to the basal region of the hair bundle and loss-of-function is associated with dysmorphic stereocilia, and vestibular and hearing dysfunction (Gagnon et al, 2006). The cib3 ortholog, encoding calcium-binding protein, has been shown to be co-expressed with tmc1 in the zebrafish inner ear HCs, with the ortholog Cib3 required for mechanotransduction in cochlear HCs (Liang et al, 2021; Giese et al, 2023; Smith et al, 2023). Expression of the gene orthologs anxa5a and Anxa5 is highly conserved among vertebrate HCs, despite unknown functional significance of the protein in auditory HCs (Krey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the high-confidence orthologs clic5a (Clic5), encodes an intracellular chloride channel protein that localizes to the basal region of the hair bundle and loss-of-function is associated with dysmorphic stereocilia, and vestibular and hearing dysfunction (Gagnon et al, 2006). The cib3 ortholog, encoding calcium-binding protein, has been shown to be co-expressed with tmc1 in the zebrafish inner ear HCs, with the ortholog Cib3 required for mechanotransduction in cochlear HCs (Liang et al, 2021; Giese et al, 2023; Smith et al, 2023). Expression of the gene orthologs anxa5a and Anxa5 is highly conserved among vertebrate HCs, despite unknown functional significance of the protein in auditory HCs (Krey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cib2 was highly expressed in IHCs and OHCs, while both cib2 and cib3 were expressed in zHCs. Patterned co-expression of tmc subtypes with cib2 and cib3 among extrastriolar and striolar zHCs was recently described (Smith et al, 2023). Describing the identities and functional interactions among the components of the mechanotransduction channel in stereocilia continues to be an area of research interest and, with their underlying similarities, zebrafish can serve as an ideal model organism.…”
Section: Expression Of Gene Orthologs Among Zebrafish and Mouse Hcs R...mentioning
confidence: 99%
“…Genetic studies have revealed that these two types of hair cells rely on different Tmc combinations for MET-short cells rely on Tmc2a while tall cells rely on Tmc2b and Tmc1 (Smith et al, 2020). More recent mRNA in situ studies have validated this Tmc requirement and shown that tmc2a, tmc2b, tmc1 are expressed in just tall cells, while tmc2a is only expressed in short cells (Smith et al, 2023). Interestingly, this work also demonstrated that cib2 is expressed broadly in tall and short hair cells, while cib3 showed more restricted expression in tall hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…Profiling of neonatal vestibular hair cells through qPCR, scRNA-seq, and single-cell proteomic analyses of chicken utricle hair cells showed Tmc1 expression clustered in extrastriola hair cells, whereas Tmc2 was found predominantly in striolar hair cells ( 12 , 13 ). Additionally, in zebrafish, homologs tmc1 , tmc2a , and tmc2b assemble in different hair cell subtypes with distinct morphologies ( 14–16 ). Taken together, these results support the hypothesis that there may be regional differences in Tmc1 expression in mice, or unique expression based on hair cell type.…”
Section: Introductionmentioning
confidence: 99%